Variation in Seed and Growth Characteristics of Normal and Quality Planting Stock of Important Fuelwood and Fodder Tree Species of Garhwal Himalayas - Mishra, Ashutosh; Nautiyal, S.; Nautiyal, D. P. (Indian Forester, 2009)
A study on seed and growth characteristics of different fuelwood and fodder tree species of Garhwal Himalayas was carried out to find out the suitable species for higher biomass production on the basis between normal and quality planting stock. The data indicated that quality planting stock attained the maximum growth as compared to the normal planting stock. Species like Grewia optiva, Terminalia chebula, Ficus gibbosa, Albizia lebbek, Kydia calyciana and Bauhinia purpurea were better in terms of growth at the nursery stage and may be given priority under the fuelwood and fodder yielding tree species of the area.